Quality of life in adults with X-linked hypophosphataemia (XLH): Preservation of emotional well-being despite significant limitations in physical domains - Pinedo-Villanueva, R; Turner, A; Barrett, J; Cooper, C; Javaid, M (Springer, 2017)
We aimed to describe the quality of life of adult patients with X-linked hypophosphataemia (XLH) using the SF-36 measure and to compare it to patients with osteoarthritis (OA) and United Kingdom population norms.